Discovery and Development of Hepatitis C Virus Inhibitors Targeting the NS5A Protein - Yu, Zhuangzhuang; Zhao, Liwen; You, Qi-Dong (Mini Reviews in Medicinal Chemistry, 2015)
Hepatitis C virus infection is a major health and economic burden worldwide. The standard of care is associated with low sustained virological response and some adverse effects. As an important component of all-oral direct-acting antiviral regimes, inhibitors of NS5A demonstrate potent pan-genotypic activity in vitro and in vivo. This review summarized the discovery and development of NS5A inhibitors, including the early chemotypes for which resistance maps to the NS5A protein, as well as first- and second-generation NS5A inhibitors and other analogues. The mechanism of action of NS5A inhibitors and related clinical trials were also described.
Keywords: direct-acting antiviral